Alterações no sistema renina angiotensina e de peptídeos natriuréticos induzidas pela ovariectomia e envelhecimento em ratas wistar - Luciana Barbosa Firmes (2012)
Objective: Ovariectomy (OVX) has been the primary rodent model to examine effects of ovarian hormone loss observed in menopause. However, this model does not discriminate the specific impact of loss of ovarian hormone and aging for menopause model. The purpose of this study was to compare the effect of ovariectomy (OVX) in young and aged rats on body weight, mean blood pressure (MBP), Natriuretic Peptides (SPN) and Renin Angiotensin System (RAS). Methods: Young (3 months) and old (16 months) female Wistar rats were ovariectomized (OVX). Blood pressure (measured by tail cuff) and body weight were followed for 5 months. At 8 and 21 months of age the animals were decapitated and the blood was collected for measurement of ANP, angiotensins, leptin and insulin by RIA. Estradiol was evaluated by ELISA. Atrial appendages were excised for determination of ANP by RIA and quantification of ANP mRNA expression by Real Time PCR. Kidneys and adipose tissues were excised, weighed and frozen for angiotensins measurements by RIAs. The expression of renin angiotensin system components was also accessed by Real Time PCR on kidney. Results: After 5 months of OVX, a great increase in body weight was observed in young rats mainly, associated to a leptin enhance. Increase of adipose tissues weight (parametrial, retroperitoneal and inguinal) was observed after OVX in young rats but only inguinal adipose tissue was increased in aged rats. No effect of OVX on BP was observed in young or aged rats at the end of the experiment, but aged rats showed an increase in BP during the first weeks after OVX. Plasma ANP was not affected by OVX but was higher in old than in young rats. A specific age-dependent increase of all angiotensins was observed in the kidney. However, aging reduced ACE, ACE2, angiotensinogen and renin expressions in the kidney. In general OVX resulted in an increase of angiotensin peptides in adipose tissues in both young and old rats associated to it increase of weight. Conclusion: Whereas age has an important role in the changes of systemic SPN and in renal RAS, ovariectomy is an important factor in the variation of adipose tissue RAS. Thus, aging and estrogen-reduction play different and complementary roles on the effects observed in the menopause models used in this study.